Review of MaqÄsid al-SyarÄ«'ah Concerning the Fulfillment of Child Rights Post-Divorce in Budi Aji Village, Simpang Pematang District, Mesuji Regency - Hidayat, Rahmat; Jayusman, Jayusman; Efrinaldi, Efrinaldi; Sari, Rita (Al-Risalah, 2022)
Divorces is often lead to multiple violations of children's rights due to parental conflicts. Therefore, this research reviewed maqÄsid al-syarÄ«'ah on the fulfillment of children's rights after divorce in Budi Aji Village, Simpang Pematang District, Mesuji Regency. It was field research and employed a descriptive qualitative method. Data were gathered by observation, in-depth interviews, and documentation, and accompanied by inductive analysis. Subsequently, this research found that the fulfillment of children's rights following parental divorce in the village has been sub-optimal. The majority of fathers are unemployed and unable to fulfill their obligations of providing a living, attention, and affection for children. The contributing factor is the fathersâ€™ irresponsibility, which impedes the achievement of maintenance benefits to the childrenâ€™s life (hifz an-nafs). These findings may have implications for the need to increase the understanding of divorced parents regarding the fulfillment of children's rights and the importance of the role of the extended family in ensuring offspring are not neglected.